Wireless 3D-localization of animals for trait and behavior analysis in indoor and outdoor areas - Millner, Hendrik; Ebelt, Randolf; Vossiek, Martin; Schlender, Kristin; Hoffman, Gundula (IEEE MTT-S International Microwave Workshop on Wireless Sensing, Local Positioning, and RFID, 2009)
This paper describes a system for three dimensional indoor and outdoor localization of animals using a sequential Monte-Carlo-Method. A Kaiman based particle filter is used to improve the measurement quality by incorporating the dynamics of the target object. The positioning method was integrated into a system for animal behavior analysis which provides extensive features to identify habitual residence and movement patterns of the animals. © 2009 IEEE.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.wirele
Keywords: Animal localization; Positioning; Real-time location; Sequential Monte Carlo methods